Effect of a Quality Improvement Project to Reduce Noise in a Pediatric Unit. Issue 2 (March 2018) - Soubra, Maher; Harb, Yara Abou; Hatoum, Sara; Yazbeck, Nadine; Khoury, Mirna; Mansour, Elie Bou; Badr, Lina Kurdahi
Abstract: Purpose: Noise levels remain high in clinical settings, which may result in stress and sleep disruption, and can lead to immunosuppression, delayed healing, confusion, disorientation, delusions, and increased length of hospital stay. The purpose of this quality improvement project was to assess effects of a multidisciplinary noise reduction program on a pediatric unit in an acute care hospital in a developing country. Methods: A quality improvement project was carried out over 15 months in a pediatric unit. A three-phase study was conducted where the first phase included obtaining patient satisfaction ratings and recording sound levels, the second phase included implementing a noise reduction program and designing a noise detector machine, and the third phase included obtaining patient satisfaction data and recording noise levels over a 1-year period. Results: There was a significant decrease in noise of 8 A-weighted decibels when comparing the values before and after implementing the quality improvement project at t = 6.44, p < 0.000. There was no significant difference in patient satisfaction ratings. Clinical Implications: Noise in the pediatric unit exceeded recommended guidelines; however, decreasing the levels was possible and sustainable, which can improve the psychological and physiological wellbeing of hospitalized children. Abstract : Excessive noise has the potential to have negative implications for hospitalized children. This quality improvement project successfully reduced noise in a pediatric unit using a multi-step team approach over a 15-month period.